FORMULASI MANAJEMEN ZAKAT: UPAYA MENGENTASKAN KEMISKINAN DI MALUKU - Khaeril Khaeril (IAIN Ambon, 2013)
National zakat movement has been implemented in the statehood but in fact it has not been able to overcome the poverty. This study aimed to recognize (1) what programs are carried out by the Province of Maluku in order to overcome the poverty in the Maluku? (2) whether and how the Amil Zakat institutions program (Baznas) Province of Maluku in order to reduce the poverty in Maluku? (3) How the contribution of Islamic Higher Education Institutions in order to succeed the National Zakat Movement as effort to reduce the poverty in Maluku? The results shows that already many national programs that be implemented in Province of Maluku, but the data shows the poverty indicators in Province of Maluku is still high. Amil Zakat Institution (BAZNAS) in Province of Maluku has been doing the program but still not significant in overcoming the poverty in Province of Maluku. This study also provides several scenarios for Islamic higher education institutions to reduce the poverty in Province of Maluku. Keywords: zakat, zakat institutions, poverty, Maluku